Oxidative Stress in Diabetes mellitus and the Role of Antioxidants in Reducing Its Complications (Samarra Journal of Pure and Applied Science, 2026)
An imbalance between free radicals and the antioxidant systems that are essential for neutralizing them leads to oxidative stress. Reduce the accumulation of free radicals and contribute to reducing oxidative stress levels in the body, antioxidants are crucial. Type 1 diabetes results from the body's incapacity insulin secretion because the beta cells in the pancreas have been destroyed due to the autoimmune destruction of these cells, while Type 2 diabetes is caused by decreased insulin release from the pancreas. Both kinds result in high blood glucose levels, and if left unchecked, persistent hyperglycemia can cause major problems..Persistent high blood glucose promotes increased generation of free radicals via multiple metabolic pathways, involving the production of advanced glycation end products (AGEs), the hexosamine route, the polyol pathway, and glucose oxidation, all of which lead to oxidative stress. The microvascular and macrovascular problems associated with diabetes are made worse by this oxidative stress. Antioxidants are essential in this situation because they neutralize the generation of free radicals, avoiding oxidative stress and problems associated with diabetes.